Learners' English Vocabulary Knowledge Prior to Formal Instruction: The Role of Learner‐Related and Word‐Related Variables. Issue 4 (18th June 2019) - Puimège, Eva; Peters, Elke
Abstract : This study focused on the mechanisms underlying incidental second language (L2) vocabulary acquisition prior to formal instruction. We designed a cross‐sectional study to examine which learner‐related and word‐related variables affect young learners' vocabulary knowledge at the level of meaning recognition and meaning recall. We collected data from 616 Flemish children between 10 and 12 years old by using a questionnaire about learners' extramural English, an English vocabulary test, and a Dutch vocabulary test. The findings revealed that participating learners frequently engaged in activities involving English before receiving formal instruction and that their amount of extramural English increased with age. The results also showed the rate of vocabulary growth from exposure to extramural English for three contiguous age groups. Further, both word‐related and learner‐related variables predicted vocabulary knowledge. Cognateness was the most powerful predictor, followed by frequency and concreteness. We also found a positive relationship between extramural English and vocabulary knowledge. Open Practices: This article has been awarded an Open Materials badge. All materials are publicly accessible via the IRIS Repository athttps://www.iris-database.org . Learn more about the Open Practices badges from the Center for Open Science:https://osf.io/tvyxz/wiki . Abstract :